Aktivitas Antifungi Ekstrak Metanol Daun Buas-Buas (Premna serratifolia) Terhadap Jamur Diplodia sp. Pada Jeruk Siam (Citrus nobilis var. microcarpa) - Ari Hepi Yanti, Sri Wahyuni, Mukarlina (Jurnal Protobiont, 2014)
The infection of Diplodia sp. Fungi on tangerine (Citrus nobilis) causes the surface of main trunk or branches to dry up. Generally, the effort of controlling disease on plants is done by the use of synthethic pesticidies that have negative impact, so that it should be mitigated and the use of botanical pesticides should be promoted. The aim of this study was to determine the antifungal activity of methanol extract of P. serratifolia leaves toward the growth of Diplodia sp. fungi. The completely randomized design (CRD) was used on this study with 6 treatments which were control, DMSO, the extract concentrations of 25%,50%, 75%, and 100%. The result showed that the methanol extract of Premna leaves significantly affecting the growth of Diplodia sp. fungi. The concentration of 100% was the one to produce the highest inhibition percentage on Diplodia sp. fungi growth, which reached 93,31% with very strong activity.